Adverse drug reaction prevalence and mechanisms of action of first-line anti-tubercular drugs - Faisal Imam; Manju Sharma; Khalid Umer Khayyam; Naif O. Al-Harbi; Mohd. Khan Rashid; Mohammad Daud Ali; Ayaz Ahmad; Wajhul Qamar (Elsevier, 2020)
Purpose: Understanding the appearance of anti-tubercular drug-related adverse drug reactions (ADRs) in patients receiving tuberculosis (TB) treatment is important, and may be related to morbidity and mortality if not recognized early. Here, we aimed to characterize the mechanisms underlying adverse drug reactions due to combination anti-tuberculosis therapy of the Revised National Tuberculosis Control Program (RNTCP). Methods: This was a prospective observational study conducted in 9 DOTS centers of New Delhi, India. All enrolled TB patients receiving first-line tuberculosis treatment as per RNTCP guidelines were monitored for ADRs. All ADRs that appeared during the treatment were recorded and analyzed. Results: The study included 1011 TB patients on anti-TB treatment under DOTS. According to Naranjo's probability scale, of a total 351 (34.72%) reported adverse events, 102 (10.09%) were definite, 59 (5.83%) probable, 123 (12.17%) possible, and 67 (6.63%) doubtful. On the Hartwig severity scale, of the 351 adverse drug events, 225 (22.26%) were mild, 105 (10.38%) were moderate, and 21 (2.08%) were severe. Out of 102 reported adverse drug reactions, 81 (79.41%) were moderate and 21 (20.59%), while 65.28% did not experience any ADRs. Conclusions: Directly Observed Treatment (DOT) is effective and safe compared to daily treatment regimens. Patients receiving DOTS therapy needed close monitoring for adverse events. Therefore, a pharmacovigilance program should be added at the National level to accesses the adverse event incidence.